Complete genome sequence of Enterobacter sp. IIT-BT 08: A potential microbial strain for high rate hydrogen production. Issue 2 (September 2013) - Khanna, Namita; Ghosh, Ananta; Huntemann, Marcel; Deshpande, Shweta; Han, James; Chen, Amy; Kyrpides, Nikos; Mavrommatis, Kostas; Szeto, Ernest; Markowitz, Victor; Ivanova, Natalia; Pagani, Ioanna; et al.
Abstract Enterobacter sp. IIT-BT 08 belongs to Phylum:Proteobacteria, Class:Gammaproteobacteria, Order:Enterobacteriales, Family:Enterobacteriaceae . The organism was isolated from the leaves of a local plant near the Kharagpur railway station, Kharagpur, West Bengal, India. It has been extensively studied for fermentative hydrogen production because of its high hydrogen yield. For further enhancement of hydrogen production by strain development, complete genome sequence analysis was carried out. Sequence analysis revealed that the genome was linear, 4.67 Mbp long and had a GC content of 56.01%. The genome properties encode 4, 393 protein-coding and 179 RNA genes. Additionally, a putative pathway of hydrogen production was suggested based on the presence of formate hydrogen lyase complex and other related genes identified in the genome. Thus, in the present study we describe the specific properties of the organism and the generation, annotation and analysis of its genome sequence as well as discuss the putative pathway of hydrogen production by this organism.